Measurement of Similarity in Academic Contexts - Mahian, Omid; Treutwein, Marius; Estelle, Patrice; Wongwises, Somchai; Wen, Dongsheng; Lorenzini, Giulio; Dalkilic, Ahmet Selim; Yan, Wei-Mon; Sahin, Ahmet Z. (MDPI AG, 2017)
We propose some reflections, comments and suggestions about the measurement of similar and matched content in scientific papers and documents, and the need to develop appropriate tools and standards for an ethically fair and equitable treatment of authors.
Keywords: similarity; plagiarism; standards; Information Science & Library Science